1990
DOI: 10.1002/j.1460-2075.1990.tb07623.x
|View full text |Cite
|
Sign up to set email alerts
|

CPF1, a yeast protein which functions in centromeres and promoters.

Abstract: Centromeres and several promoters of Saccharomyces cerevisiae contain a highly conserved octanucleotide, RTCACRTG, called CDEI. Using biochemical, genetic and structural analyses, we show that the same protein binds in vivo to CDEI sites in centromeres and in promoters. This protein, called CPF1 for centromere promoter factor, binds DNA as a dimer. Inactivation of the gene is not lethal but leads to a partial loss of the centromere function and to a Met‐ phenotype. Changes of the chromatin structure due to ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
220
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(231 citation statements)
references
References 49 publications
11
220
0
Order By: Relevance
“…Isw1p-Myc, which is fully functional in chromatin remodeling, is described in more detail in Kent et al (40). Disruptions of the CBF1 locus were created by gene replacement as described (19). For chromatin analysis in Figs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isw1p-Myc, which is fully functional in chromatin remodeling, is described in more detail in Kent et al (40). Disruptions of the CBF1 locus were created by gene replacement as described (19). For chromatin analysis in Figs.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work has concentrated on potential Cbf1p binding motifs that occur in a gene regulatory context; a recent series of genome-wide protein localization experiments tested the binding of a variety of transcription factors to yeast promoter regions and suggested that 83% of intergenic CACGTG palindromes were likely to be bound by Cbf1p (31). Mutation of the CBF1 gene or mutation of potential CACRTG binding motifs in the regulatory DNA of the GAL2, TRP1, CYT1, PGK, RPL45, QCR8, and GSH1 genes leads to perturbation of transcriptional regulation (19,(32)(33)(34)(35)(36)(37). In addition, altered patterns of nuclease accessibility in chromatin consistent with changes in nucleosome position have been reported in association with Cbf1p binding at the TRP1 and QCR8 promoters (19,28,38), suggesting that chromatin remodeling is a general function of DNA-bound Cbf1p.…”
mentioning
confidence: 99%
“…Although KlQCR8 and KlCYC1 are functionally related genes, regulation by KlCpf1p seems to operate over them in a different way since, in the KlCYC1 promoter, the KlCpf1-binding site is included into a negative regulatory region. Opposite effects of Cpf1p on transcriptional regulation of different genes are not unexpected; in S. cerevisiae, Cpf1p may act as an activator or as a repressor of transcription in different promoters [24]). Directed mutagenesis of each of the three Cpf1p binding consensus at the KlCYC1 promoter, or combinatorial mutation of them, as well as availability of viable KlCpf1p mutants will be necessary to obtain a reliable picture of the detailed influence of KlCpf1p on KlCYC1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Cbf1 is a helix-loop-helix leucine zipper protein that binds as a homodimer directly to the CDEI-DNA element of the centromere (Bram and Kornberg, 1987;Baker et al, 1989;Mellor et al, 1990). Functional studies in haploid S. cerevisiae cells showed that Cbf1p is non-essential (Cai and Davis, 1990).…”
Section: Introductionmentioning
confidence: 99%